Production, characterization and properties of beta-glucosidase and beta-xylosidase from a strain of Aureobasidium sp. - Iembo, T. [UNESP]; Da-Silva, R. [UNESP]; Pagnocca, F. C. [UNESP]; Gomes, E. [UNESP] (My University, 2002)
beta-glucosidase and beta-xylosidase production by a yeast-like Aureobasidium sp. was carried out during solid-state and submerged fermentation using different carbon sources and crude enzymes were characterized. beta-glucosidase and beta-xylosidase gave optimum activity at pH 2.0-2.5 and 3.0, respectively. These enzymes presented maximal activity at 65 degrees, and were stable in a wide pH range and high temperatures.